Citizens' attitude toward's local government and citizen's participation in local government - Mohammadi, Seyed Hamid; Syed Abdul Rashid, Sharifah Norazizan; Ahmad, Nobaya (Marsland Press, 2010)
The purpose of this paper is to describe the citizen’s attitude toward local government and its relationship with level of participation. Participation in local government issues, requires a favorable attitude towards local government, councilors and councils’ performance in terms of efficiency. The paper is based on the study of citizens' attitude towards local government, which was carried out in Torbat Hedarieh city, Iran. The analysis of data uses Pearson correlation to determine the relationship between variables involved. The findings revealed that two level of ladder participation (Tokenism and Citizen-power) have positive and significant relationship with attitude, while Non-participation level of ladder participation has negatively significant relationship with attitude. The findings of the study imply that those respondents who have positive attitude toward local government, councilors and council performance, would have the higher tendency to be actively involved in higher levels of participation, whereas who have negative attitude toward local government, would put less effort in higher levels of participation.